2011
DOI: 10.1016/j.autneu.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adjustments induced by hypertonic saline in hemorrhagic rats: Involvement of carotid body chemoreceptors

Abstract: The peripheral hyperosmolarity elicited by intravenous infusion of hypertonic saline brings potential benefits to the treatment of hemorrhage. The neural mechanisms involved in these beneficial effects remain unknown. The present study examines the role of carotid chemoreceptors in cardiovascular responses induced by hypertonic saline after hypovolemic hemorrhage in rats. Male Wistar rats (300-400 g) were anesthetized with thiopental, and instrumented for recording of mean arterial pressure. Arterial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Previous studies demonstrated the involvement of carotid and aortic afferents in endocrine and renal responses induced by acute hypernatremia . Furthermore, Dibona et al .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies demonstrated the involvement of carotid and aortic afferents in endocrine and renal responses induced by acute hypernatremia . Furthermore, Dibona et al .…”
Section: Discussionmentioning
confidence: 92%
“…The baroreflex and chemoreflex are important mechanisms that are used to recover homeostasis after changes in extracellular volume and composition occur [10], [26], [57]. Previous studies demonstrated that the hypertension that was induced by HS was significantly higher in sinoaortic,denervated rats [10].…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) detects variations in the volume, tonicity, and composition of the extracellular compartment through various peripheral and central receptors [2][5]. Once detected,these changes trigger a set of responses that reestablish physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently examined the role of carotid body chemoreceptors in the effect of hypertonic saline, inactivating the carotid body chemoreceptors by ligation of the carotid body arteries. That study indicated that the nervous organ glomus caroticum has a prominent and determinant role in the effect of hyperosmotic saline (26). When the function of carotid body chemoreceptors was blocked, leaving all nerves in the area functional, hyperosmotic saline failed to restore arterial pressure.…”
Section: Role Of Carotid Afferents In Responses To Ecf Changesmentioning
confidence: 92%